Muslim Institutions of Learning (Madrasa) in Ayyubid and Mamluk Syria - Hatim Mahamid (Research Aspects in Arts and Social Studies Vol. 8, 2023)
This study focuses on dealing with the rise and spread of the madrasa, in terms of motives and methods, as an institution of higher education in religious sciences in the Ayyubid and Mamluk Syria (Bilad al-Sham) (1187-1516) by relying on endowments (waqf) as charitable acts. The madrasa began to appear and spread in Syria, as a higher institution for religious education, since the Zengids’ rule (1127-1174), then it grew during the Ayyubid and Mamluk eras in the main cities in Syria, especially that served the political centers, such as Damascus, Aleppo, Jerusalem, and others. In his study, G. Makdisi dealt with such topics, but he focused on the rise of the madrasa as an institution of learning in Eleventh Century Baghdad [1,2]. In the second half of the Mamluk era, various factors emerged that directly affected the decline in the madrasa’s work and its maintenance in Syria, even though, several attempts were made to renew and redevelop endowments (waqf) and madrasas. Through the discussion in this paper, it is concluded that the motives for contributing waqf and madrasas in Syria during the Mamluk era were apparent as political motives, while during the Zangid and Ayyubid periods, it was noticeable that religious motives were stronger.